Hydroxyethyl Starch-Based Functionalization of Gold Nanorods: A Possible Alternative to Polyethylene Glycol as a Surface Modifier. (23rd March 2021) - Pandey, Asmita; Khadka, Sujan; Wan, Ying
Abstract : PEGylation refers to the process of functionalizing nanoparticles with polyethylene glycol (PEG) to avoid unspecific uptake by the mononuclear phagocyte system and prolong the circulation half-life of nanomedicines. Immunogenicity and nonbiodegradability are the major limitations in PEGylation that can be resolved by substituting PEG with biofriendly polymers, such as hydroxyethyl starch (HES). In the current study, thiolated hydroxyethyl starch (HES-SH, 130/0.4) was harnessed to stabilize gold nanorods (AuNRs) and compared with PEG-SH-coated AuNRs at different aspects of characterization and photothermal analysis. Our results confirm that AuNRs were functionalized successfully with both HES-SH and PEG-SH, where the initial spectra and colloidal stability of gold nanorods were restored after functionalization. In addition, the photothermal conversion stability of gold nanorods was maintained during both HESylation and PEGylation without affecting the heat generation. In summary, we presume that HES-SH can be used as a surface modifier to stabilize gold nanorods and might be used as a promising alternative to PEG.